Medical School Applicant Characteristics Associated With Performance in Multiple Mini-Interviews Versus Traditional Interviews: A Multi-Institutional Study. (July 2018) - Henderson, Mark C.; Kelly, Carolyn J.; Griffin, Erin; Hall, Theodore R.; Jerant, Anthony; Peterson, Ellena M.; Rainwater, Julie A.; Sousa, Francis J.; Wofsy, David; Franks, Peter
Abstract : Purpose: To examine applicant characteristics associated with multiple mini-interview (MMI) or traditional interview (TI) performance at five California medical schools. Method: Of the five California Longitudinal Evaluation of Admission Practices consortium schools, three used TIs and two used MMIs. Schools provided retrospective data on 2011–2013 admissions cycle interviewees: age, gender, race/ethnicity (underrepresented in medicine [UIM] or not), disadvantaged (DA) status, undergraduate GPA, Medical College Admission Test (MCAT) score, and interview score (standardized as z score; mean = 0; SD = 1). Adjusted linear regression analyses, stratified by interview type, examined associations with interview performance. Results: The 4, 993 applicants who completed 7, 516 interviews included 931 (18.6%) UIM and 962 (19.3%) DA individuals; 3, 226 (64.6%) had only 1 interview. Mean age was 24.4 (SD = 2.7); mean GPA and MCAT score were 3.72 (SD = 0.22) and 33.6 (SD = 3.7), respectively. Older age, female gender, and number of prior interviews were associated with better performance on both MMIs and TIs. Higher GPA was associated with lower MMI scores ( z score, per unit GPA = −0.26; 95% CI = −0.45, −0.06) but unrelated to TI scores. DA applicants had higher TI scores ( z score = 0.17; 95% CI = 0.07, 0.28) but lower MMI scores ( z score = −0.18; 95% CI = −0.28, −0.08) than non-DA applicants. Neither UIM status nor MCAT score was associated with interview performance. Conclusions: These findings have potentially important workforce implications, particularly regarding MMI performance of DA applicants, and illustrate the need for other multi-institutional studies.